Curahan Kerja Wanita Pada Usahatani Padi Sawah di Desa Beha Kecamatan Tabukan Utara Kabupaten Kepulauan Sangihe - Debora Philip; Charles R. Ngangi; Olfie L.S. Benu; Welson M. Wangke (Universitas Sam Ratulangi, 2014)
ABSTRACTDebora Philip. The Flurry of Female Labor of Rice Farming in Beha Village, North Tabukan Sub District, Sangihe Regency under guidance of Charles R. Ngangi as a Chairman, BenuOlfie L. S. and Welson M. Wangke as Members.The objective of this research is to know flurry of female labor in rice farming from nursery work, land preparation, planting, weeding, pest and disease control until harvest. The data used in this study is primary data and secondary data. The primary data obtained through interviews based on questionnaire to the farmers directly and secondary data obtained from relevant department such as Agricultural Crops, Estate Plantation, and Forestry service of Sangihe Regency, office of north Tabukan Sub District. In this study the variables measured is the amount of labor in women who used the low land rice farming. The data analyzed descriptively.The results showed that the flurry of female labor in rice farming in general was in the work of planting, weeding and harvesting although the available data showed that the flurry of female labor also exists in the number of female workers in lowland rice farming village in the District brassiere North Tabukan Sangihe Regency was 22.64 person – days per ha or 28.03 % in one growing season of rice farming.